(untitled) (Educational Perspectives Magazine (REPED), 2023)
Blindness is a problem about which there is scarce. But infortunately it is even fewer when the mechanisms of human interrelation that allow the construction of relating codes to the sexuality are involved. The main reason this investigation was sustained in the lack of theoretical information that bases the about the sexuality of the people. The ignorance of the elements that Ínter act in the social construction and the generic identity o f these young persons. The purpose of this investigation has been to know the narrative of young blind men and women with different educational level about the problem gender identity.